2013
DOI: 10.1002/elps.201200552
|View full text |Cite
|
Sign up to set email alerts
|

Mass transport in a porous microchannel for non‐Newtonian fluid with electrokinetic effects

Abstract: Quantification of mass transfer in porous microchannel is of paramount importance in several applications. Transport of neutral solute in presence of convective-diffusive EOF having non-Newtonian rheology, in a porous microchannel was presented in this article. The governing mass transfer equation coupled with velocity field was solved along with associated boundary conditions using a similarity solution method. An analytical solution of mass transfer coefficient and hence, Sherwood number were derived from fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…(7)) and approximate velocity profile (Eq. (18a)) shows that the profiles are close and <2% deviation [29,30].…”
Section: Description Of the Velocity Profile (Within Concentration Bomentioning
confidence: 87%
See 2 more Smart Citations
“…(7)) and approximate velocity profile (Eq. (18a)) shows that the profiles are close and <2% deviation [29,30].…”
Section: Description Of the Velocity Profile (Within Concentration Bomentioning
confidence: 87%
“…The boundary conditions in nondimensional form are represented as follows: atx*=0;c*=1, aty*=0;Penormalwcm*Rnormalr+4|c*y*y*=0=0, aty*;c*=1.The wall concentration ()cnormaly=0=cm is related with real retention ( R r ) as: Rnormalr=1cpcm=1cnormalp*cnormalm*.Equation can be solved using the similarity parameter . The concentration profile can be expressed in terms of the similarity parameter as: where the constant B is represented as .…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bryce and Freeman (2010) experimentally showed that the viscoelasticity of a polymer solution may induce extensional instability in electroosmotic microflow at straight regions of microchannel. Evident electroosmotic applications of non-Newtonian fluids comprise liquid pumps (transport systems) in microfluidic systems (Mondal and De, 2013); micromixing (Cho and Chen, 2012; Hadigol et al , 2011) and heat transfer systems (Zhao and Yang, 2012; Cho et al , 2012; Chen, 2011; Sadeghi et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting accumulation of the ions in the downstream section of the channel sets up its own electric field (streaming field), which generates the conduction current (I cond ), that flows back against the direction of the pressure-driven flow. Thus, the net ionic current (I ionic ) is the combination of the streaming current and conduction current [27]. Hence,…”
Section: Streaming Fieldmentioning
confidence: 99%